Differences in Knowledge of Preconceptional Mothers about Breast Examination (Breaking) as Pre-and-Post Explanation Breast Cancer Prevention - Sopia, Lela; Tuti Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims:  To determine the level of knowledge of pre-conception mothers on breast self-examination (BSE) as prevention of pre and post-breast counseling in Karang Mukti Village, Karang Bahagia District, Bekasi Regency. Methods:  Research Methods: Quasi-experimental with one group pretest-posttest design. Quasi-experimental research is a form of experimental research that does not have a control group (Notoatmodjo, 2018). Results:  It is known that the BSE Correlation value is 0.923 with a p-value of 0.000, so it can be said that there is a relationship between the Pre-Test Conscious and Post-Test Conscious variables. And the Breast Cancer Correlation is 0.668 with a p-value of 0.000, so it can be said that there is a relationship between the variables of Pre-test for breast cancer and Post-test for breast cancer. Conclusion:  There is a relationship between the frequency of conscious measurement with breast cancer before and after the intervention with a p value of 0.000